NEWSPAPER MEANS OF MASS INFORMATION AND THEIR ROLE IN FORMING A SOCIO-CIVIL POSITION OF INHABITANTS OF PRYKARPATTIA - Хороб, С. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the history of establishment and development of newspaper periodicals of the Precarpathian land, their influence on the formation of a socio-civil position, on the upbringing of a national, patriotical and spiritual Christian attitude of the inhabitants of the region. The utilized archived materials, as well as numerous newspaper publications convincingly prove importance of «paper» mass media for the Precarpathians – both in the past and present. It also concentrates attention on information politics of former and contemporary newspapers that came out in different times in Prykarpattia.